Molecular epidemiology of avian influenza viruses and avian coronaviruses in environmental samples from migratory bird inhabitants in Bangladesh - Khatun, Most. Nahida; Tasnim, Shadia; Hossain, Md. Riabbel; Rahman, Md. Ziaur; Hossain, Md. Tofazzal; Chowdhury, Emdadul Haque; Parvin, Rokshana (Frontiers in Veterinary Science, 2024)
Migratory birds are a natural reservoir for major respiratory viruses such as the avian influenza virus (AIV) and the avian coronavirus (AvCoV). Transmission of these viruses from migratory birds to domestic birds increases the prevalence of those diseases that cause severe economic and public health concerns in Bangladesh. The study focused on active surveillance of major respiratory viral pathogens in migratory birds, molecular identification of the viruses, and their phylogenetic origin. To conduct this study, 850 environmental samples (830 fecal samples, 10 soil samples, and 10 water samples) were collected during three consecutive winter seasons from three divisions (Dhaka, Sylhet, and Mymensingh) and pooled according to the year of collection and locations, resulting in a total of 184 tested samples. Using gene-specific primers and probes in TaqMan-and SYBR Green-based RT-qPCR assays, the samples were screened for AIV and AvCoV, respectively. Out of the 184 pooled samples, 37 were found to be positive for these respiratory pathogens. Furthermore, out of the 37 (20.11%) positive respiratory pathogens, 11.96% were AIV (n = 22) and 8.15% were AvCoV (n = 15). For the first time in Bangladesh, AIV H4N2, H4N6, and AvCoVs have been found in fecal samples from migratory birds through surveillance. Phylogenetic analyses of the HA and NA genes of AIV and the polymerase gene (Orf 1) of AvCoV revealed that these strains share a close phylogenetic relationship with the isolates from wild birds in Europe and Asia. The Bangladeshi strains with Eurasian ancestry might pose a significant threat to migratory birds flying through the Asian flyways. They might also be a potential source of virus introduction and spread to poultry raised on land. These findings emphasize the significance of ongoing AIV and AvCoV surveillance in migratory birds in Bangladesh.